If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -7 = -19 Reorder the terms: -7 + 2k = -19 Solving -7 + 2k = -19 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2k = -19 + 7 Combine like terms: -7 + 7 = 0 0 + 2k = -19 + 7 2k = -19 + 7 Combine like terms: -19 + 7 = -12 2k = -12 Divide each side by '2'. k = -6 Simplifying k = -6
| 4(x+6)-2=6(x+4)-10 | | 5(2x-1)+4=4 | | 6(x-5)=36-5x | | 8+(6n+9N)= | | 2(x+4)=4x+34 | | 42x-30x^2=0 | | 4(3x-7)+8=2x+10 | | 10x-5+4=4 | | 4*(1/2+x)=3 | | 0.075(p+2000)=0.08p+0.03(2000) | | 8=-(x+4) | | 2x-3=42-7x | | 5+3r=5r-14 | | 1+1/2= | | 6h=-30 | | (x+5)(x+5)=0 | | 7(7p-4)=-175 | | 2x-3=32-7x | | 160+x= | | 0.1(50)=0.2(60+x)-0.4x | | x^3-3x^2-45x+94=0 | | 0.3x-0.5(5)=0.2 | | -40=-5d | | 11(x+3)=-2(2x+6) | | -6-3=3-6y | | 2x+3=10+x | | -r+(3r^2+1)r=4 | | 5x-12x-7=8 | | -8=f/5 | | 38-4x=6(x+8) | | -3=k+3 | | (2t^2+7t-6)-(3t^2-11t-9)=0 |